RESPON PERTUMBUHAN SERTA PRODUKSI TERUNG UNGU (Solanum melongena L.) TERHADAP PEMBERIAN POC AZOLLA DAN TSP - Cecep Nurhidayat; Zulkifli; M. Nur; Putri Lukmanasari (UIR Press, 2024)
This research determines the response of purple eggplant (Solanum melongena L.) to the application of triple superphosphate (TSP) and Azolla Liquid Organic Fertilizer (POC). The study was carried out at the Experimental farm of the Faculty of Agriculture at Riau Islamic University, Pekanbaru. The experimental design was a factorial randomized arrangement featuring two main components: Azolla POC applied in four volumes (0, 200, 400, dan 600 ml per polybag)) and TSP fertilizer administered in four quantities (0, 2,5, 5, dan 7,5 g per tanaman). This design resulted in 16 treatment combinations, each replicated three times, totaling 48 experimental units. The study included 192 polybag plants, with four plants assigned to each unit and two of those sampled for analysis. The parameters measured included plant height, age at flowering, age at harvest, number of fruits per plant, weight of individual fruits, total fruit weight per plant, and number of remaining fruits on each plant. After conducting statistical analyses, the data were evaluated using the BNJ test at a 5% significance level. The results of the research on the combination of Azolla POC and TSP were significant on the observed parameters. Specifically, plant height, age at flowering, age at harvest, number of fruits per plant, weight of individual fruits, total fruit weight per plant, and number of remaining fruits on each plant; the best treatment was a combination of Azolla POC 600 ml polybag and TSP 7.5 g/plant. The main effect of Azolla POC was significant on all parameters; the best treatment was Azolla POC 600 ml polybag. The main impact of TSP was substantial on all observed parameters; the best treatment was a TSP application of 7.5 g per plant